Penerapan Web Service dalam Mengintegrasikan IoT dengan Platform Investasi Berbasis Website dan Mobile Android - Amrulloh, Arif; Saputra, Wahyu Andi; Arini, Ratih Windu; Pane, Sayyid Yakan Khomsi (STMIK Palangkaraya, 2024)
The industrial revolution 4.0 which is occurring rapidly has resulted in changes in various fields, IoT is a technology that is currently widely used to automate processes in everyday life. In this research, IoT was used to monitor the development of goat livestock in Dermaji village. The problem with IoT development is that when you want to display data or results obtained, IoT does not work well if the information displayed is less interactive and difficult for end users to understand, so a solution needs to be created to display the results obtained by developing website and mobile-based applications. The aim of this research is to integrate an IoT platform with Android mobile-based websites and applications by implementing a RESTful web service API. Web and mobile application development uses the RAD method which consists of several stages, namely the design stage of system requirements, system design and implementation into a programming language. In integrating IoT with websites and mobile, RESTful web service technology is applied. The result of this research is an IoT platform that is integrated with website and Android mobile based applications.